Characterization and evaluation of maize landraces (Scientia Agricola, 2002)
The choice of germplasm plays an important role in any plant breeding program. The goals of this paper were to characterize and to evaluate the genetic potential of IAPAR's maize (Zea mays L.) landraces for breeding purposes. Characterization of 25 landraces of maize for endosperm type and kernel color is shown. In 1998/99, experiments using randomized complete block designs with two replications were carried out in three locations of Brazil (Londrina-PR, Ponta Grossa-PR, and Anhembi-SP). For grain yield, the most promising landraces were GI156 (Cayano Sobrália) and GI045 (Tupy Pyta Sopé). Their performances for grain yield represent 86.9% and 84.6% of the hybrid AG122 yield, respectively, and were of the same magnitude of the adapted varieties (BR-105 and BR-106).